The competition between discount stores and COOP in Northern Hungary: a case study - Sikos, Tamás T.; Kovács, Csaba József (Geographica Pannonica, 2022)
In the past decades, the expansion policy of hard discounters is receiving increasing scientific attention. One of the main reasons of their success is location choices, which needs geographical thinking and knowledge of socio-economic environment. Although it has key importance to gain high purchase power territories in this competition, each company have to implement their own geo-strategy. While discount stores are operating in the town, national franchise small stores have an extensive network in the rural area. This paper is a case study which deals with competition of hard discounters and Coop in Northern Hungary.